A concepção de infância presente no Manifesto dos Pioneiros da Educação Nova de 1932: a presença do pensamento de John Dewey (1859-1952) - Oliveira, Marco Aurélio Gomes de (2011)
The central objective of this dissertation is to investigate the historical, philosophical conception of infancy that is present in the document A reconstrução educacional no Brasil: Ao povo e ao governo. Manifesto dos Pioneiros da Educação Nova (The reconstruction of education in Brazil: to the people and to the government. The Pioneer Manifest of New Education), with the intent of analyzing how much the thought of the New School of Dewey influenced the movement of pedagogical renewing in Brazil in the 1920s and 1930s. In order to do that, this paper is organized in two parts: in the first the theory of the philosopher john Dewey (1859-1952) is analyzed with the purpose of understanding how infancy, conceived by the American educator, is related to a greater social project that involves a renewing in the educational and social fields. In the second part, we analyze how the conceptions of infancy, education, democracy and freedom defended by Dewey contributed to the construction of the speech of the Pioneers of the New School for a new infancy that would be able to participate in the process of national reconstruction. It is possible, by the means of analysis, to perceive that the conception of infancy that is in the document defended by the Pioneers represents a consensus among them, in the way that the New Deweyan School, despite being extremely relevant, shares its position with other theories, specially, the positivism. When concluding this dissertation it was possible to notice that the ideas of the New School that were so noteworthy in the first half of the 20th century are still alive in the current Brazilian educational scenery. Although they are marginalized in the official documents, their presence in the pedagogical speeches that value individuality, freedom of expression, syllabus flexibilization proves that. Therefore, the Deweyan expression to learn how to learn is one of the main points to understand how updated they still are in the pedagogical proposals.